МОДЕЛЬ ВЕКТОРНОГО ГИСТЕРЕЗИСА ПРИ ПЕРИОДИЧЕСКОМ ЭЛЕКТРОМАГНИТНОМ ПОЛЕ - Петухов, И.С. (Інститут електродинаміки НАН України, Київ, 2013)
A vector hysteresis model for the symmetric magnetization cycle, based on a combination of fractional rational functions was proposed. The model explicitly expresses dependences of field strength from induction. The model is intended to be used with finite element method and represents the influence of the saturation of ferromagnetic on the magnitude of the magnetic field and its wave form in two orthogonal directions. The dependence of losses on the magnetic induction under condition of rotational magnetization is in good agreement with known experimental data. References 17, figures 5.